Evaluation Reaction Support Breaker Wave Floating on the System mooring Catenary with Variation Position Fairlead - Hotma Harapan Saragih; Roesdiman Sogiarso; Indra Noer Hamdhan (Journal of Business, Social and Technology, 2026)
Research This evaluate reaction support on the breaker wave floating measuring (55 × 30 × 10) m moored effective draft 5 m use chain catenary system studlink as many as 10 pieces (5 left + 5 right ). Analysis numeric done using SAP2000 for variation fairlead elevation z=-5, " " 0, " " 5 m and angle uniform string θ=7.5^∘, " " 7.63^∘, " " 8^∘, " " 10^∘, " " 12^∘, " " 13^∘, " " 15^∘. Condition loading covering wave (H = 2.5 m; T = 5.5 s), load dead , load life , components hydrodynamics peak , load wind , buoyancy, and pretension per rope 666,667 kN. The results show that horizontal component X dominates reaction support with range around 240 – 276 MN, whereas The lateral component of Y ranges from 37 – 112 MN. The component vertical Z shows variation big and change sign depends fairlead elevation : Z value can be reach mark positive extreme until hundreds thousand MN in low fairlead cases and values negative large on high fairlead . Findings This confirm influence significant catenary configuration ( fairlead elevation and angle rope ) against distribution style to anchorage and highlight the need verification output numeric ( especially component vertical ) and extraction reactions per component burden before design end of anchorage. Recommendation covering analysis pretension sensitivity , simulation mooring time domain dynamics , and studies capacity land base for critical anchors .